1999
DOI: 10.1006/dbio.1998.9113
|View full text |Cite
|
Sign up to set email alerts
|

Cell Fate Specification in theDrosophilaSalivary Gland: The Integration of Homeotic Gene Function with the DPP Signaling Cascade

Abstract: Salivary gland formation in the Drosophila embryo is linked to the expression of the homeotic gene Sex combs reduced (Scr). When Scr function is missing, salivary glands do not form, and when SCR is expressed everywhere, salivary glands form in new places. However, not every cell that expresses Scr is recruited to a salivary gland fate. Along the anterior-posterior axis, the posteriorly expressed proteins encoded by the teashirt (tsh) and Abdominal-B (Abd-B) genes block SCR activation of salivary gland genes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 64 publications
0
38
0
1
Order By: Relevance
“…Recent studies demonstrated the possible involvement of Schnurri and SEM-4 in the growth factor signaling pathway and mesoderm development. Schnurri is shown to be necessary for the signaling pathway of Drosophila decapentaplegic, a member of the transforming growth factor ␤ superfamily most closely related to the vertebrate bone morphogenetic proteins BMP-2 and BMP-4 (2,15,17). Genetic analysis using C. elegans has demonstrated that SEM-4 is required for the development of neuronal cells and mesodermal cell lineage (4,8).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated the possible involvement of Schnurri and SEM-4 in the growth factor signaling pathway and mesoderm development. Schnurri is shown to be necessary for the signaling pathway of Drosophila decapentaplegic, a member of the transforming growth factor ␤ superfamily most closely related to the vertebrate bone morphogenetic proteins BMP-2 and BMP-4 (2,15,17). Genetic analysis using C. elegans has demonstrated that SEM-4 is required for the development of neuronal cells and mesodermal cell lineage (4,8).…”
Section: Discussionmentioning
confidence: 99%
“…7). At the top of the hierarchy are the genes that regulate the decision to form SGs: Scr-Exd-Hth, in the absence of the negative regulators Dpp, Tsh and Abd-B (Panzer et al, 1992;Henderson et al, 1999;Henderson and Andrew, 2000). ScrExd-Hth activate expression of CrebA, Sage, Fkh and Hkb, which function to maintain and implement the SG fate decision by maintaining their own expression, the expression of each other and of terminally differentiated gene products.…”
Section: Research Articlementioning
confidence: 99%
“…SGs are initially specified by the combined activities of the homeotic protein Sex combs reduced (Scr) and its co-factors Extradenticle (Exd) and Homothorax (Hth) (Panzer et al, 1992;Ryoo and Mann, 1999;Henderson and Andrew, 2000). All three factors are essential for SG formation and ectopic expression of Scr, the one spatially limited component, can induce SG cell fates in the subset of ectodermal cells that do not experience activated Dpp signaling (dorsal cells) or express neither Teashirt (Tsh) (parasegments 3-14) or Abdominal B (Abd-B) (parasegment 15) (Panzer et al, 1992;Henderson et al, 1999). In the SG secretory cells, Scr and its co-factors activate the expression of several transcription factors, including Fkh, the bZip protein CrebA, the bHLH protein Sage and the SP1-like protein Huckebein (Hkb) (Panzer et al, 1992;Andrew et al, 1997;Myat and Andrew, 2000b).…”
Section: Introductionmentioning
confidence: 99%
“…During embryogenesis, tsh has been shown to participate in the patterning of the epidermis (Fasano et al, 1991;Roder et al, 1992;Andrew et al, 1994;de Zulueta et al, 1994;Gallet et al, 1998Gallet et al, , 2000Robertson et al, 2004) and the development of the salivary glands (Henderson et al, 1999) and the gut (Mathies et al, 1994;Waltzer et al, 2001;Saller et al, 2002), and tsh null mutants are embryonic lethal (Fasano et al, 1991). The Drosophila genome contains also a tsh paralogue, tiptop (tio; Laugier et al, 2005).…”
Section: Introductionmentioning
confidence: 99%